Parentage verification and genetic diversity of the Arabian and Thoroughbred horse populations in Türkiye using microsatellite analysis - Yarali, Cevdet; Ozsensoy, Yusuf; Koseman, Abdurrahman; Seker, Ibrahim; Toprak, Burhan; Zengin, Kemal (Gesellschaft Schweizer Tierarztinnen & Tierarzte, 2023)
This study aimed to determine the effectiveness of parentage verification in Arabian and Thoroughbred horses in Turki-ye using microsatellite markers. A total of 813 Arabian and 959 Thoroughbred horses were genotyped using a total of 17 microsatellite markers. The mean effective number of alleles was 3,34 and the mean number of alleles was 7,41 in Arabian horses. It was calculated that the mean He and Ho values in Arabian horses were 0,677 and 0,680, respective-ly. The mean effective number of alleles was 3,55 and the mean number of alleles was 6,59 in Thoroughbred horses. It was calculated that the mean Ho and He values in Thor-oughbred horses were 0,697 and 0,684, respectively. When the studied Arabian and Thoroughbred horse populations are considered as a single population, the mean FIT, FST and FIS values were found to be 0,063, 0,074 and, - 0,011, re-spectively. Also, 4 loci in Arabian horses and 3 loci in Thor-oughbred horses significantly deviated from HWE. The mean PIC value was 0,63 in Arabian horses and 0,64 in Thoroughbred horses. As a result; the microsatellites includ-ing the most informative 15 and 9 loci had a total value of > 0,9999 (11 and 7 loci > 0,999) in each population for PE - 1 and PE - 3, respectively. It has been concluded that parentage verification and genetic identification can be made successfully in the Arabian and Thoroughbred horse populations by using the microsatellite markers panel.
Vérification de la filiation et de la diversité génétique des populations de chevaux arabes et de pur-sang en Turquie à l’aide de l’analyse des microsatellites]; [Überprüfung der Abstammung und genetischen Vielfalt der Araber- und Vollblutpferde in der Türkei mittels Mikrosatellitenanalyse]; [Verifica dell’ascendenza e diversità genetica delle popolazioni di cavalli Arabi e Purosangue in Turchia mediante analisi microsatellitare
Keywords: Arabian horse; genetic variation; microsatellite; parentage verification; Thoroughbred horse